MUTAF ONE-STAGE TECHNIQUE FOR CONGENITAL CONSTRICTION RINGS – SAFE AND EFFECTIVE: Congenital constrition rings - Vlahovic, Aleksandar; Zivkovic, Milana; Begovic, Ninoslav; Dizdarevic, Ivan; Vlahovic, Natasa (Medical Research, 2023)
Introduction: The congenital constriction ring is a rare congenital malformation that especially affects the limbs. It is associated with fibrous bands that could encircle, strangle or amputate some parts of the fetus. However, there are only a few techniques described for the correction of this anomaly. We aim to present a successeful treatment of congenital constriction ring in a one-stage Mutaf technique.Patient Review: In our report, we presented two infants with congenital constriction rings. In the first case, we presented the infant with a constriction band on the right arm accompanied by deformity of the distal part and with lymphoedema. In the second case, we presented the infant with multiple constriction bands on the distal part of the right leg with clubfeet and with severe lymphoedema. They were both treated with one-stage Mutaf technique using rectangular dermofat grafts to fill the groove. Using this technique we obtained a normal limb contour, with no edema or neurovascular compromise. Filling the groove with the rectangular dermofat flaps parallel to the relaxed skin tension lines, provides a better scar in comparison with multiple Z- or W-plasty techniques. Additionally, the benefit of one-stage procedure is a reduction of the surgical and psychological trauma of patients and their parents, less time spent under general anesthesia and less amount of anesthetic the patient takes, and less cost of hospitalization.Conclusion: We find Mutaf techinque is effective and safe technique for treatment of congenital constriction rings.
Keywords: Amniotic Band, Surgery, Technique